Social development theory & practice - Midgley, James (Sage, 2014)
Walking through social development's key theoretical principles and practice strategies, this book shows how it promotes peoples' wellbeing not only in the Global South, where it first emerged, but in the Western countries as well. It covers: -- Definitions and an historical evolution of social development -- Key theoretical debates around social well-being, human rights and social justice -- Social development practice such as human capital interventions, community development and cooperatives, asset building, employment creation policies and programmes, microenterprises and social planning among others -- Future challenges; global poverty, international aid and trade, and global inequality, conflict and injustice. Complete with international examples drawn from around the world, Social Development: Theory and Practice demonstrates how social development theory translates into practical application. This book is ..